The Effectiveness of EFI Scanner Video Media in Enhancing Understanding of EFI System Diagnostics in Light Vehicle Electrical Maintenance - Miftah, Miftah; Juni Rohman; I Gusti Made Adnyana (Classroom Experiences, 2024)
This study aims to evaluate the feasibility of video media and its effectiveness in enhancing students understanding of using a scanner for diagnosing Electronic Fuel Injection (EFI) systems in the subject of light vehicle electrical maintenance. The research employs a one-group pre-test post-test design. Validation tests conducted by subject matter experts and media experts rated the video media as highly appropriate for instructional use. The average pre-test score was 57.50, which increased to 77.00 in the post-test, resulting in a learning improvement gain of 0.46. Hypothesis testing with α = 0.05 and degrees of freedom (df) = 31 yielded t = 23.49, which is greater than the critical value ttable = 2.04, leading to the rejection of H0. This indicates a significant improvement in students understanding of EFI system diagnostics facilitated by the video media. The effectiveness of the video media in enhancing learning was quantified at 27.69%. However, other contributing factors, such as varying physiological and psychological conditions of learners, environmental influences, infrastructure, and curriculum design, also played a role in the learning outcomes.